Strategi Pengembangan Usaha Pengolahan Gula Aren Berdasarkan Metode Analisis SWOT (Studi Kasus Desa Weninggalih, Kecamatan Sindangkerta) - Putri Saiba; Purwanti, Rina; Firmansyah, Efrin (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2023)
processing of palm sugar is one of the products of plantation commodities that have very high economic value and have good prospects for development so that there is a great opportunity to improve the economy of the people of a region. one of them is in Weninggalih village, West Bandung Regency. Geographically, the Weninggalih area is surrounded by the Mount Halu mountain area so it has various kinds of natural resources. One of the results of its natural sources, namely palm trees. This palm sugar processing activity is still classified as a home industry, including the small or medium business group. Primary source of family income and support for agricultural activities which constitute the majority of the main livelihoods of rural communities. The purpose of this research is to develop a strategy for the development of the palm sugar industry in Weninggalih village using the SWOT analysis method by knowing the internal (strengths and weaknesses) and external (opportunities and threats) factors that can influence its development strategy. This type of research is research with qualitative and quantitative descriptive methods using SWOT analysis. The results of the SWOT matrix analysis research carried out in the palm sugar business are based on the SO strategy, namely good quality palm sugar will affect market competition, good raw material consistency will affect the processing of palm sugar which is increasing and greatly influences the improvement of the family economy and has good working partner in palm sugar processing.